Agriculture policy in India a study of the living conditions of rural villager’s due to the green revolution - Chanti, Guguloth (International Journal of Scientific Research and Management (IJSRM), 2017)
This paper examines the challenges and challenges of small holding farming in India. Small Holders Agriculture, Holders and Challenges, including the role of small holders, differential systems, institutional support and information requirements for improving employment opportunities, agricultural growth, cultivation practices, small holders, agriculture, small holders, productivity performance, small value chains, valuable chains, food security, Future options. It offers lessons from India experience on small holding farming to other countries. The current research paper seeks to establish a link between structural, technical and institutional policy reforms, which are responsible for sustainable agricultural development. Although India has recently achieved considerable growth rates, it still faces agricultural plight. Therefore, this paper is currently attempting to expose agricultural productivity and its future prospects. Some secondary information has been collected to analyze agriculture's realistic scenario and various policy programs by the government. With the analysis of secondary information and extensive literary reviews, I gave some suggestions for the growth and productivity of this sector.